2019
DOI: 10.31202/ecjse.450790
|View full text |Cite
|
Sign up to set email alerts
|

Bor Nitrür Partikülleriyle Takviyelendirilmiş Vinil Ester Matrisli Kompozitlerin Mekanik Özelliklerinin İncelenmesi

Abstract: Son yıllarda inorganik partiküllerle takviyelendirilmiş polimer matrisli kompozitler yaygın bir şekilde kullanılmaktadır. Yapılan çalışmaların birçoğu, polimer malzemelere inorganik yapıların ilavesiyle elde edilen hibrid malzemeler üzerine yoğunlaşmıştır. Bu çalışmada, bor nitrür partikül takviyeli vinil ester kompozit malzemeler üretilmiştir. Matris malzemesi olarak vinil ester reçinesi kullanılmıştır. Takviye malzemesi olarak ise ortalama 70 nm boyutlarında olan hegzagonal bor nitrür partikülleri kullanılmı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It is evaluated that various additives that can be made to the matrix material in composite materials can reduce the surface to surface transfer amount and thus increase the wear resistance [20][21][22][23] In the study, it was determined that due to the lubricating effect of boric acid, its wear resistance increased with the addition of the matrix material. In addition, by adding boric acid to the matrix material to obtain hybrid composite material, the average tensile strength values have increased significantly depending on certain ratios by weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evaluated that various additives that can be made to the matrix material in composite materials can reduce the surface to surface transfer amount and thus increase the wear resistance [20][21][22][23] In the study, it was determined that due to the lubricating effect of boric acid, its wear resistance increased with the addition of the matrix material. In addition, by adding boric acid to the matrix material to obtain hybrid composite material, the average tensile strength values have increased significantly depending on certain ratios by weight.…”
Section: Discussionmentioning
confidence: 99%
“…After a certain amount of boron component reinforcement, it has been also shown in the literature that this components has a negative effect on average tensile strength or does not affect it at all. Boztoprak and Kartal [20] showed in their study that the tensile strength value decreased due to the increase in the boron nitride ratio. Navaneethakrishnan et al [5] showed in their study that %1 by weight boron nitride reinforcement increased tensile strenght value on the other hand %2 by weight boron nitride reinforcement decreased.…”
Section: Effects Of Using Boric Acid As Reinforcement For Tensile Strengthmentioning
confidence: 94%
“…However, there was a significant decrease in tensile strength when 44% hBN was used. Boztoprak et al [10] studied the mechanical properties of composite materials with vinyl ester matrix and BN particles. As a result of the research, there was an increase in the hardness of composite samples and the abrasion resistance and impact strengths were improved.…”
Section: Investigation Of Flexural Properties Of Hexagonal Boron Nitr...mentioning
confidence: 99%